2016
DOI: 10.1158/1535-7163.mct-16-0068
|View full text |Cite
|
Sign up to set email alerts
|

The BRAF Inhibitor Vemurafenib Activates Mitochondrial Metabolism and Inhibits Hyperpolarized Pyruvate–Lactate Exchange in BRAF-Mutant Human Melanoma Cells

Abstract: Understanding the impact of BRAF signaling inhibition in human melanoma on key disease mechanisms is important for developing biomarkers of therapeutic response and combination strategies to improve long-term disease control. This work investigates the downstream metabolic consequences of BRAF inhibition with vemurafenib, the molecular and biochemical processes that underpin them, their significance for antineoplastic activity, and potential as noninvasive imaging response biomarkers.1 H NMR spectroscopy showe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
50
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 51 publications
5
50
0
1
Order By: Relevance
“…16 Our in vitro hyperpolarization results confirm and extend the work of Beloueche-Babari and colleagues: they observed a BRAFi-mediated drop in the HP pyruvate-to-lactate exchange in the BRAF-mutated cell line WM266.4, but not in cells harbouring wild-type BRAF, therefore, intrinsically resistant to BRAFi. 17 By using a BRAFiresistant clone derived from the parental cell line, 30 we have shown that the effect in term of reduced glycolysis and label exchange is specific to sensitive cells and may not be present in BRAF-mutated F I G U R E 5 BRAFi reduced hypoxia in vivo, without affecting the vessel density. A, Representative EPR spectra obtained from a mouse prior treatment (top) and after 5 d of treatment with vemurafenib (bottom).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Our in vitro hyperpolarization results confirm and extend the work of Beloueche-Babari and colleagues: they observed a BRAFi-mediated drop in the HP pyruvate-to-lactate exchange in the BRAF-mutated cell line WM266.4, but not in cells harbouring wild-type BRAF, therefore, intrinsically resistant to BRAFi. 17 By using a BRAFiresistant clone derived from the parental cell line, 30 we have shown that the effect in term of reduced glycolysis and label exchange is specific to sensitive cells and may not be present in BRAF-mutated F I G U R E 5 BRAFi reduced hypoxia in vivo, without affecting the vessel density. A, Representative EPR spectra obtained from a mouse prior treatment (top) and after 5 d of treatment with vemurafenib (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…17 Within the scope, immunocompetent mice would allow to obtain a more thorough picture of the cross-talk between cancer cells and immune cells. 17 Within the scope, immunocompetent mice would allow to obtain a more thorough picture of the cross-talk between cancer cells and immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay between cancer cell metabolism and response to targeted therapies too warrants further research. A growing number of reports are linking nutrient metabolism (glucose, glutamine) and melanoma cells responsiveness to BRAF inhibition while at the same time it is clear that the MAPK pathway regulates glycolysis and oxidative phosphorylation (16,(135)(136)(137)(138)(139)(140)(141). All these gaps in our understanding of melanoma biology and the potential of managing MAPK inhibitor schedules with drug-holidays or combination with immunotherapies shows that there is room for improvement to better manage advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Such a quantitative approach can be utilized to predict global metabolic states of cancer cells under various conditions. Melanoma cells upon BRAF-inhibition have been shown to induce an enhanced oxidative phosphorylation (Delgado-Goni et al, 2016;Haq et al, 2013;Smith et al, 2016) . Byproducts of augmented mitochondrial activity are reactive oxygen species (ROS), and this metabolic switch promotes oxidative stress in cells (Cesi et al, 2017;Zorov et al, 2014) .…”
mentioning
confidence: 99%